Предмет: Алгебра, автор: aarturchic251155

2.Спростіть вираз; а). Х(Х-1)-(Х+3)(Х+2);  б). (Х-5)(Х+8)-(Х+4)(Х-1). Дам максимум балов срочно​

Ответы

Автор ответа: Аноним
2

1) x(x-1)-(x+3)(x+2)=x^{2} -x-(x^{2} +2x+3x+6)=x^{2} -x-(x^{2} +5x+6)=x^{2} -x-x^{2} -5x-6=-6x-6\\\\ 2)(x-5)(x+8)-(x+4)(x-1)=x^{2} +8x-5x-40-(x^{2} -x+4x-4)=x^{2} +8x-5x-40-(x^{2} +3x-4)=x^{2} +8x-5x-40-x^{2} -3x+4=0-36=-36

Автор ответа: SirWallon
1

Объяснение:

Задание 1

x(x - 1) - (x + 3)(x + 2) =  {x}^{2}  -  x -  {x}^{2}  - 2x - 3x - 6 =  - 6x - 6 =  - 6(x + 1)

Задание 2

(x - 5)(x + 8) - (x + 4)(x - 1) =  {x}^{2}  + 8x - 5x - 40 -  {x}^{2}   + x - 4x + 4 =  -36

Похожие вопросы